2013
DOI: 10.1111/dmcn.12149
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory function in children with severe motor disorders using night‐time postural equipment

Abstract: Aim Night‐time postural equipment (NTPE) can prevent hip subluxation in children with severe motor disorders (SMDs). However, it is unclear how it affects ventilatory function. The aims of the study were to determine how NTPE use affects ventilatory function and to compare night‐to‐night variability of ventilatory function in children with SMDs and typically developing healthy children. Method Fifteen NTPE users (six males, nine females), aged 1 to 19 years (mean age 8y 7mo) alternated sleep condition between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Therefore, this is not a study of the overall prevalence of these factors in children and young people with CP, nor does it address the unique psychosocial or emotional aspects that determine families’ capacity to deal with the associated challenges of everyday life. Nevertheless, this study adds a home‐based perspective to the previous studies which report the wide diversity of concerns in relation to sleep for this population . It shows that, in clinical practice, identification of only one or two sleep concerns may greatly underestimate the extent of the problems.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this is not a study of the overall prevalence of these factors in children and young people with CP, nor does it address the unique psychosocial or emotional aspects that determine families’ capacity to deal with the associated challenges of everyday life. Nevertheless, this study adds a home‐based perspective to the previous studies which report the wide diversity of concerns in relation to sleep for this population . It shows that, in clinical practice, identification of only one or two sleep concerns may greatly underestimate the extent of the problems.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐nine papers used the GMFCS only to describe participants . Eleven other papers used the GMFCS only to define eligibility criteria . While reliability and validity of GMFCS have been demonstrated in children with CP, none of these articles reported reliability or validity of these GMFCS categorizations in other conditions/clinical descriptions.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 118 papers, 76 did not mention that the GMFCS was developed specifically for use with children with CP or discuss its measurement properties . Twenty noted that the GMFCS was created for children with CP but did not justify its application to their condition/clinical description . Three of these papers stated that the GMFCS had not been validated in their condition/clinical description of interest, or that none of their participants had CP .…”
Section: Resultsmentioning
confidence: 99%
“…Dawson et al . have measured oxygen saturation (SO 2 ) and tcPCO 2 in the blood of children with SMD and have shown that these children have a less stable ventilation during the night compared to typically developing children.…”
mentioning
confidence: 99%
“…They have also measured tcPC0 2 but conclude that this measurement contains errors and in general is overestimating actual arterial (a) P a CO 2 . Due to metabolic CO 2 production in the living cells of the epidermis and circulatory disturbances that permit the gas to accumulate in the tissue, tcPCO 2 is higher than P a CO 2 .…”
mentioning
confidence: 99%